(untitled) (Research, Society and Development, 2018)
Thinking about future series, a new search for alternative means for development and environmental protection. The school environment favors the presence of a sustainable learning process, especially when children are exposed to sensory situations that present the learning process, more vulnerable to environmental influences (CAPRA, 2008). Environmental Education at Foundation Crê-Ser (João Monlevade), through the construction of a system for comparing organic results of school education, using them in an ecological garden developed as children. The project was carried out by Engineers without Frontiers (ESF) of João Monlevade, between April 2018. Environmental Education workshops were held, where 30 people were found among children and present in order to cultivate the germination process through experiment with beans, with softener pills, they chose as vegetables for cultivation. The children planted the seedlings, with young people and staff. During the mentioned steps, they were involved every time, which presupposes a set of general considerations is the same as maintaining the environment indicators, in addition, the educators already perceived the access to the garden as a tangible didactic resource for the application and understanding disciplinary content. Universities have timely extended this scenario to apply their academic data.